Ecosystem services survey data (Wessex BESS) - Graves, Anil; McGinlay, James (Cranfield University, 2018)
Dataset used in the paper "Do charismatic species groups generate more cultural ecosystem service benefits?", DOI 10.1016/j.ecoser.2017.07.007. Also used in an upcoming paper, expected for publication early 2018.
Keywords: Social Scientific Research'; 'cultural services'; 'Ecosystem Function'; 'Social and Cultural Geography'; 'Social and Community Psychology'